Eavesdropping on animals : what we can learn from wildlife conversations - Bumann, George (2024)
"In Eavesdropping on Animals, George Bumann shares the fascinating stories and insights he has gained from studying wildlife around the world for more than forty years, the last twenty of which have been spent leading popular programs on animal language and intelligence in Yellowstone National Park. Bumann shares tips, tricks, and advice for readers living in urban, suburban and rural areas and clearly shows us that you don't need an exotic vacation or a biology degree to have transformative wildlife encounters. Listening to and observing creatures in your own backyard, on nearby trails, and in local parks, seashores, fields, and forests can lead to extraordinary experiences and a profound sense of belonging."--